The effect of trust in government and tax literacy on PBB-P2 taxpayer compliance with perception of tax fairness as a mediating variable in Southeast Minahasa Regency - Tumimomor, Cherril Angelia; Warongan, Jessy D. L.; Budiarso, Novi S. (Yayasan Widyantara Nawasena Raharja, 2026)
Trust in government and adequate tax literacy are frequently identified as key determinants of taxpayer compliance; however, empirical findings remain inconclusive, particularly at the local tax level. This study examines the direct effects of trust in government and tax literacy on PBB-P2 (Land and Building Tax for Rural and Urban Areas) taxpayer compliance and investigates the mediating role of perceived tax fairness in Southeast Minahasa Regency, Indonesia. Using a quantitative approach, data were collected from 108 registered PBB-P2 taxpayers and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that trust in government has a positive but insignificant direct effect on taxpayer compliance, whereas tax literacy and perceived tax fairness have positive and significant effects. Furthermore, perceived tax fairness fully mediates the relationship between trust in government and taxpayer compliance and partially mediates the relationship between tax literacy and taxpayer compliance. These findings highlight that perceptions of fairness constitute a critical psychological mechanism through which institutional trust and individual tax knowledge are translated into compliant behavior. The study contributes to the tax compliance literature by emphasizing the strategic importance of fairness-oriented tax administration and targeted tax literacy programs at the local government level.